90.1k views
4 votes
R(x) = –x² + 3x s(x) = 2x + 1

(s – r)(x) =

User BorisMoore
by
4.9k points

2 Answers

4 votes

r(x) = –x² + 3x

s(x) = 2x + 1

(s – r)(x) is simply the difference of these functions. Subtract r(x) from s(x):

(s - r)(x) = s(x) - r(x)

(s - r)(x) = 2x + 1 - (-x² + 3x)

(s - r)(x) = 2x + 1 + x² - 3x

(s - r)(x) = x² - x + 1

User Miledy
by
3.9k points
5 votes

Answer:

(s-r)(x) = x²-x+1

Explanation:

We have given two functions.

r(x) = -x²+3x and s(x) = 2x+1

We have to find the difference of two functions.

(s-r)(x) = ?

The formula to find the difference of two functions is :

(s-r)(x) = s(x)-r(x)

Putting the value of given functions in above formula, we have

(s-r)(x) = (2x+1)-(-x²+3x)

(s-r)(x) = 2x+1+x²-3x

(s-r)(x) = x²+(-3+2)x+1

(s-r)(x) = x²+(-1)x+1

(s-r)(x) = x²-x+1 which is the answer.

User Jessie Richardson
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.